Identification and functional analysis of a novel yeast small nucleolar RNA. - Dandekar, T (1993)
snR31 is a RNA species of 225 nt. which has the trimethyl guanosine cap structure typical of small nuclear RNAs (snRNAs) and yeast small nucleolar RNAs (snoRNAs), and is associated with the nucleolar proteins fibrillarin (NOP1) and GAR1. On sub-nuclear fractionation, snR31 behaves like other snoRNAs, and is enriched in a nucleolar fraction. The SNR31 genomic locus is close to the SNR5 locus, which encodes another snoRNA. The two genes are divergently transcribed with 217 bp separating the transcription start sites. Disruption of the SNR31 gene does not detectably impair growth in a haploid strain. Analyses of pre-rRNA processing in wild-type and snr31- strains shows some accumulation of the 35S primary transcript in the mutant, indicating a mild impairment of the initial steps in pre-rRNA processing.